The school for scandal. - Sheridan Richard Brinsley (1966)
Lyceum Theatre, 1966-67 season, APA-Phoenix (A project of Theatre Incorporated), T. Edward Hambleton, managing director presents the APA Repertory Company, Ellis Rabb, artistic director ... directors Vinnette Carroll, Keene Curtis, Hal George, John Houseman, Donald Moffat, Stephen Porter, Ellis Rabb, scenery designed by James Tilton, costumes designed by Nancy Potts, lighting by Gilbert V. Hemsley, Jr. "The School for Scandal," by Richard Brinsley Sheridan, directed by Ellis Rabb, associate director Hal George, scenery designed by James Tilton, costumes designed by Nancy Potts, lighting by Gilbert V. Hemsley Jr.